2019
DOI: 10.1177/2516608519846034
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors, Etiology, and Clinical Outcome of Ischemic Stroke in Young Adults Admitted in a Tertiary Care Hospital in India

Abstract: Background: Ischemic stroke in young adults is becoming a rising concern with the increase in vulnerability to traditional risk factors and changing lifestyles. Aim: An overview of risk factors, classification, and clinical outcome of ischemic stroke in young adults (19 to 45 years) has been presented. Methods: Data fulfilling the study criteria from the stroke registry between June 2014 and June 2017 were collected, and a detailed proforma was taken that included history, clinical examination, and routine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…In our study the mean age was 62 years which was lesser in comparison to a similar study done by Volans.P et al 14 which showed a mean age of 69 years and another study done by Werner Hacke et.al 15 that showed a mean age of 64.9 years. An Indian study done by Ramasamy et al, 16 showed mean age of 59 years which was consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
“…In our study the mean age was 62 years which was lesser in comparison to a similar study done by Volans.P et al 14 which showed a mean age of 69 years and another study done by Werner Hacke et.al 15 that showed a mean age of 64.9 years. An Indian study done by Ramasamy et al, 16 showed mean age of 59 years which was consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
“…A study from North India revealed that the mean age of stroke patients was 39. 8 Similar multicentric study from Asian countries had mean age of 40.8. 9 This finding may be due to the study being predominantly done in the younger age group of patients.…”
Section: Discussionmentioning
confidence: 84%
“…We have included 61 studies in our systematic review, conducted across various states in India, estimating the various lifestyle risk factors for stroke ( Table 1 ). 13 73 Out of 61, 56 studies were conducted and 58 were published after 2000. In 51 studies, patients were enrolled from the hospital-based stroke registries (HBSR) maintained in various treatment settings across India, while in 10 studies, the enrollment was using population-based stroke registries (PBSR).…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the studies included in the meta-analysis are summarized in Table 2 . The meta-analysis included 36 studies, out of which two studies 31 , 66 were multicentric and the remaining included data from various states of the Indian subcontinent (North: 13, 13 , 17 , 20 , 29 , 33 , 39 , 49 , 51 , 54 56 , 69 , 61 South: 14, 14 , 19 , 23 , 40 , 45 , 48 , 53 , 59 , 62 , 63 , 65 , 68 , 70 , 71 East: 3, 28 , 36 , 6 West: 2, 47 , 57 and Central: 2 25 , 41 ). The majority of the studies were published in the past decade.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation